Strategies for Enhancing Co-existence in Diverse Social Groups - Sharma, Lok Raj; Khulal, Rupak (International Research Journal of MMC, 2024)
Co-existence is a pleasing word to converse, but an intricate word to believe and follow in a real-life situation. This article aims to suggest effective strategies for enhancing co-existence in diverse social groups. To attain these objectives, the secondary data were congregated through a comprehensive review on co-existence and the strategies for enhancing co-existence from books, journal articles, and website materials published from the year 1971 to 2024. The article employed exploratory research and operated thematic analysis as its qualitative research design. It identifies. promoting inclusive education, encouraging intercultural dialogue, supporting community engagement initiatives, implementing anti-discrimination policies, promoting social integration programs, facilitating interfaith initiatives, encouraging multicultural policies, supporting civil society organizations, and promoting economic inclusion as the effective strategies for enhancing co-existence in diverse social groups. This article provides exquisite insights for leaders, policymakers and citizens, emphasizing that the feeling of co-existence is essential for the overall well-being of a nations and its citizens.